Social Adversity and Mental Health among Individual Client in University of Calabar Teaching Hospital, Nigeria - Njirinze, Chinenye Juliet; Eyong, Butum Bassey (ESUT JOURNAL OF SOCIAL SCIENCES, 2020)
The study examines social adversity and mental health in University of Calabar Teaching Hospital. The study specifically examine the extent to which social adversity indicators such as bereavement, divorce and life-threatening-disease have a significant effect on individual mental health in University of Calabar Teaching Hospital, Cross River State, Nigeria. Literature was reviewed based the variables of the study while the Frustration and Aggression theory was employed as the study’s theoretical framework. The study adopted the Expost Facto and Cross sectional survey design. The population comprised of inpatients in mental health clinic and patient with chronic related illnesses. Sample of the study was 51 but 50 were retrieved after field work. Instruments for data collection were questionnaire and case history (Interview). The questionnaire was titled; Questionnaire for Social Adversity and mental health conditions in University of Calabar Teaching Hospital. Data analysis was done using Logit Regression, ANOVA and Multiple linear regressions. To elicit data for the study, a consent letter was sent to University of Calabar Teaching Hospital Research and Ethical Committee. The letter approval gave the researcher the leverage to elicit data for the study. From the analysis, findings revealed that, death of a love one, marital divorces and life-threatening-disease have a significant effect on individual mental health outcome in University of Calabar Teaching Hospital, Nigeria. From the finding, it was recommended among others that Nigerian government need to invest in mental health and employ more professional doctors and medical social workers to help in the provision of care and support for those facing social adversity. It was concluded that, a lot of awareness is needed against most of the social stigma painted at ill people and the perception we hold toward people under social adversity. This is observable even among and outside health care professionals, including mental health professionals, stigma remains a huge issue